Synthesis, crystal structure, structure-activity relationships, and antiviral activity of a potent SARS coronavirus 3CL protease inhibitor - Yang, Syaulan; Chen, Shu-Jen; Hsu, Min-Feng; Wu, Jen-Dar; Tseng, Chien-Te K.; Liu, Yu-Fan; Chen, Hua-Chien; Kuo, Chun-Wei; Wu, Chi-Shen; Chang, Li-Wen; Chen, Wen-Chang; Liao, Shao-Ying; et al. (Journal of medicinal chemistry, 2006)
A potent SARS coronavirus (CoV) 3CL protease inhibitor (TG- 0205221, K-i = 53 nM) has been developed. TG- 0205221 showed remarkable activity against SARS CoV and human coronavirus ( HCoV) 229E replications by reducing the viral titer by 4.7 log (at 5 mu M) for SARS CoV and 5.2 log (at 1.25 mu M) for HCoV 229E. The crystal structure of TG- 0205221 (resolution = 1.93 angstrom) has revealed a unique binding mode comprising a covalent bond, hydrogen bonds, and numerous hydrophobic interactions. Structural comparisons between TG- 0205221 and a natural peptide substrate were also discussed. This information may be applied toward the design of other 3CL protease inhibitors.